Dupilumab Efficacy and Safety in Adolescents with Moderate-to-Severe Atopic Dermatitis: A Case Series - Adrien Mareschal; Eve Puzenat; François Aubin (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)